1997
DOI: 10.3109/00016489709117984
|View full text |Cite
|
Sign up to set email alerts
|

Two-phase Endolymphatic Hydrops: A New Dynamic Guinea Pig Model

Abstract: The classical guinea pig model for Meniere's disease, in which endolymphatic hydrops was achieved by destruction of the endolymphatic sac and obliteration of the endolymphatic duct, is a non-physiological profound model with shortcomings in relation to Meniere's disease as seen in patients. We developed a more subtle animal model; the two-phase endolymphatic hydrops. This model is based on a combination of chronic endolymphatic sac dysfunction, induced by slight destruction of the most distal part of the endol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
42
1
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 19 publications
5
42
1
1
Order By: Relevance
“…However, abnormal OCT findings in EH, such as Reissner's membrane distension, were confirmed by comparison with pathologic analyses in previous studies, 9,16 and the abnormal findings of OCT images in this study were consistent with those of previous studies. Both 2-D and 3-D OCT images clearly showed the abnormal EH findings, indicating the potential of OCT as an effective tool for analyzing cochlear pathologies.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…However, abnormal OCT findings in EH, such as Reissner's membrane distension, were confirmed by comparison with pathologic analyses in previous studies, 9,16 and the abnormal findings of OCT images in this study were consistent with those of previous studies. Both 2-D and 3-D OCT images clearly showed the abnormal EH findings, indicating the potential of OCT as an effective tool for analyzing cochlear pathologies.…”
Section: Discussionsupporting
confidence: 82%
“…It is difficult to identify EH in patients with Meniere's disease because clinical examinations such as the auditory brainstem response (ABR) and caloric tests only provide functional information regarding a damaged cochlea or vestibule. Consequently, many studies have attempted to investigate the pathophysiology of Meniere's disease and the presence/absence of EH using histological examination in animal models, [11][12][13][14][15][16][17] with the most popular model being that induced by surgical ablation of the endolymphatic duct and sac. A surgical technique proposed by Kimura requires penetration of the brain's protective covering, leading to an increase in morbidity and mortality associated with penetration of the central nervous system.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study using an animal model of MD, Dunnebier et al 20 reported chronic ES dysfunction induced by destruction of the ES, and acute stress-induced endolymph production by aldosterone administration revealed severe degrees of hydrops in the cochlea. 20 In this investigation, we successfully developed a new clinically relevant animal model for MD, in which desmopressin (a VP type 2 receptor agonist) was administered after electrocauterization of the ES.…”
mentioning
confidence: 99%
“…20 In this investigation, we successfully developed a new clinically relevant animal model for MD, in which desmopressin (a VP type 2 receptor agonist) was administered after electrocauterization of the ES.…”
mentioning
confidence: 99%
“…Partant de cette hypothèse, des modèles expéri-mentaux dits «biphasiques» ont cherché à comparer les pourcentages d'hydrops endolymphatiques obtenus chez le cochon d'Inde soit par dysfonctionnement isolé du sac (diminution de la vascularisation et du drainage lymphatique), soit lorsque celui-ci est associé à d'autres perturbations de l'homéostasie de l'endolymphe. Une lésion isolée du sac entraîne un hydrops dans 40 % des cas, alors que ce pourcentage est de 90 % lorsqu'une administration de minéralocorticoïdes est associée [15], ces hormones étant supposées augmenter la sécrétion de l'endolymphe cochléo-vestibulaire. Hydrops endolymphatique au cours de la maladie de Ménière.…”
Section: Hydrops Endolymphatique Expérimentalunclassified